Does expression of estrogen receptor, progesterone receptor, and HER2 in atypical breast lesions predict a subsequent clinically significant event? - Tjoe, Judy A; Neitzl, Gary F; Singh, Maharaj; Last, Brittany S; Marx, James; Kansra, Sanjay (Advocate Aurora Health Institutional Repository, 2014)
Background: Atypical ductal hyperplasia (ADH) and atypical lobular hyperplasia (ALH) increase breast cancer risk 3-5 fold. Risk reduction strategies include intense radiographic surveillance, medical, or surgical prophylaxis, all with associated side effects. Thus, identifying predictors of future breast cancer associated with atypia would limit aggressive treatment to only those patients at highest risk for disease progression. Given that lifetime estrogen exposure is a risk factor for breast cancer, and human epidermal growth factor receptor-2 (HER2) gene amplification is linked to breast pathogenesis, we tested whether expression patterns of estrogen receptor (ER), progesterone receptor (PR), and HER2 at initial diagnosis of atypia predicted a subsequent clinically significant event (SCSE), defined as another occurrence of atypia, in situ, or invasive carcinoma. Methods: Patients with an initial diagnosis of ADH and/or ALH were retrospectively identified. 19 women who developed a SCSE (cases) were matched to 45 women with no SCSE for at least 5 years after the diagnosis of atypia (controls). Archived tissue from cases and controls were subjected to ER, PR, and HER2 immunohistochemistry. ER and PR were reported using Allred score (0 to 8). HER2 was reported as negative (0-1+), equivocal (2+) or positive (3+). Atypia with HER2 (2+) or (3+) scores were subject to SISH to confirm gene amplification. Results: There was no significant difference in expression of ER (mean Allred: cases = 7.26 ± 0.35; controls = 6.91 ± 0.43) or PR (mean Allred: cases = 6.95 ± 0.43; controls = 6.57 ± 0.34). >90% of both cases and controls were HER2 negative (0-1+). Longitudinal assessment of ER, PR, and HER2 in patients who developed a SCSE revealed that three of 19 cases presented with HER2 overexpression; however SISH analysis revealed no gene amplification. Interestingly, ER/PR expression decreased in three of seven patients with atypia who later developed an invasive malignancy. Conclusions: ER and PR expression do not predict ...